2006
DOI: 10.1016/j.molcel.2006.07.019
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Repair Helicases XPD and FancJ Have Essential Iron-Sulfur Domains

Abstract: DNA helicases are essential components of the cellular machinery for DNA replication, recombination, repair, and transcription. The XPD and FancJ proteins are related helicases involved in the nucleotide excision repair (NER) and Fanconi anemia repair pathways, respectively. We demonstrate that both proteins have a conserved domain near the N terminus that includes an iron-sulfur (Fe-S) cluster. Three absolutely conserved cysteine residues provide ligands for the Fe-S cluster, which is essential for the helica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
344
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(362 citation statements)
references
References 37 publications
15
344
1
Order By: Relevance
“…The functional significance of the ISC and CIA machineries has gained progressive interest since a number of essential cytosolic and nuclear Fe/S proteins have been identified, the function of which may critically depend on their Fe/S cofactors [29][30][31] . In fact, the presence of essential Fe/S clusters in these proteins may explain the indispensable character of mitochondria and the ISC and CIA machineries for cell viability 29 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The functional significance of the ISC and CIA machineries has gained progressive interest since a number of essential cytosolic and nuclear Fe/S proteins have been identified, the function of which may critically depend on their Fe/S cofactors [29][30][31] . In fact, the presence of essential Fe/S clusters in these proteins may explain the indispensable character of mitochondria and the ISC and CIA machineries for cell viability 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Ribosome maturation and protein translation require the 2Â [4Fe-4S] cluster-containing protein Rli1, which resides in both cytosol and nucleus 29,32 . Other essential Fe/S proteins are involved in the integrity, maintenance and repair of DNA, but the presence of Fe/S clusters in these proteins in vivo has not been verified yet 30,31 . Replication of the lagging strand critically depends on the primase complex, which includes the Fe/S cluster-containing large subunit Pri2 (ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is now evidence that mutations specifically in the iron-sulfur cluster domain of XPD result in TFIIH instability, thus leading to TTD (28,30). Similarly, mutations in the analogous region on the related FancJ gene (which also encodes a helicase with an iron-sulfur cluster) causes predisposition to early onset breast cancer (25,32,33). We have demonstrated that the [4Fe-4S] cluster in Sulfolobus acidocaldarius (Sa)XPD is redox-active, with a redox potential equivalent to that of BER proteins EndoIII and MutY [approximately 80 mV vs. normal hydrogen electrode (NHE)] (34).…”
mentioning
confidence: 99%